Skin Viscoelasticity: Physiologic Mechanisms, Measurement Issues, and Application to Nursing Science - Everett, Janine S. (2012)
Skin is the primary interface between health care providers and patients and is assessed clinically to predict physiological stability or instability. The biomechanical properties of human skin, most notably elasticity and viscoelasticity, are critical to its protective function. In this article, the authors describe the physiological basis for skin elasticity and viscoelasticity. The authors discuss the role of viscoelasticity in nursing science and consider avenues for scientific exploration of the skin’s biomechanical properties, including applications in pressure ulcer research, injury, and healing. They also discuss the Cutometer(®) as one option for measurement of viscoelasticity in clinical and bench research protocols.